High-Frequency Ultrasound: A Novel Diagnostic Tool to Measure Pediatric Tonsils in 3 Dimensions. (November 2019) - Kay-Rivest, Emily; Saint-Martin, Christine; Daniel, Sam J.
Objective: A wide variety of pathologies can affect the palatine tonsils. Ultrasound is a commonly used modality for assessing head and neck masses in children; however, its use in tonsillar evaluation has not been widely explored. The objective of this study was to measure 3-dimensional tonsillar size with ultrasound, in centimeters, and correlate these measurements with actual ex vivo dimensions on pathology specimens. Study Design: We performed a prospective cohort study. Setting: The study was set in a tertiary care children's hospital. Subjects and Methods: Children undergoing tonsillectomy were included in the study. Transcervical high-frequency ultrasonography (HFU) was performed prior to surgery to obtain 3-dimensional measurements of the right and left palatine tonsils. Mean sizes were compared to ex vivo tonsil measurements and correlations were obtained. Results: Seventy-five consecutive children underwent a transcervical HFU, with a total of 150 tonsils analyzed. The mean differences between HFU and pathology measurements were −0.08 cm and −0.24 cm for the right and left craniocaudal axes, −0.19 cm and −0.18 cm for the right and left mediolateral axes, and 0.05 cm and 0.03 cm for the right and left anteroposterior axes. Correlation coefficients between ultrasound and pathology measurements were all above 0.5. Conclusion: HFU can accurately measure the size of pediatric tonsils in 3 dimensions.